Nutrition Management for Acute Stroke with Right-Sided Hemiparesis: A Case Study - Md Said, Norfarhana; Mohd Fahmi Teng, Nur Islami; Mohamed Denil, Nurnajwa; Rahim, Hazelin Abdul (Jurnal Gizi dan Pangan, 2024)
This case study aims to report on the nutrition management of acute stroke with right-sided hemiparesis using an approach of early enteral feeding intervention to prevent malnutrition. Mr. R, a 77-year-old Malay man was admitted to the hospital due to an acute stroke with right hemiparesis with underlying disease of Atrial Fibrillation (AF), hypertension, type 2 Diabetes Mellitus (DM), Chronic Kidney Disease (CKD) stage 3b, and significant Peripheral Artery Disease (PAD). His BMI was 24kg/m2 with a weight of 67kg and height of 1.67m, and he was presented with abnormal blood results. All his vital signs were normal, and he appeared lethargic. The patient was on bolus Nasogastric (NG) feeding via Ryle’s tube with polymeric formula. Inadequate enteral nutrition infusion related to infusion volume not yet reached, as evidenced by a 47% energy and 60% protein adequacy feeding history. The polymeric formula was changed to a diabetic-specific formula for better blood sugar control, and feeding was given according to the patient's needs. Mr. R required at least 70% of 1,675 kcal of energy and 53.6 g of protein (0.8 g/kg body weight) to prevent malnutrition. The patient was still on Ryle’s tube feeding and already achieved the targeted energy and protein requirements. Before being discharged, the patient was allowed orally, and a sample menu was given as guidance to avoid weight loss and muscle wasting during longterm recovery. This case highlights the importance of early enteral feeding support in stroke recovery and the need to prioritize meeting nutritional needs in stroke patient care. Mr. R showed improvement in health and nutrition and concluded that early and focused enteral nutrition support can lead to improved results and better quality of life for stroke survivors.